GREEN ECONOMY INTEGRATION IN CLIMATE CHANGE MITIGATION AND ENVIRONMENTAL CONSERVATION IN INDONESIA - Era Purike (INJOSEDU: International Journal of Social and Education, 2026)
This article examines green economy integration as Indonesia's main strategy in climate change mitigation and environmental preservation through a comprehensive literature review approach. Two main discussions cover (1) the implementation of the Low Carbon Development Initiative (LCDI), Second Nationally Determined Contribution (SNDC) 2025, and the 23% renewable energy target in the 2025-2029 RPJMN for GHG emission reduction, and (2) the synergy of the circular economy, biodiversity conservation, and community-based practices in agro-industrial waste management, green tourism, and ecosystem restoration. The research results confirm the effectiveness of the green economy in creating 1.8 million green jobs, forestry net sinks, and green Special Economic Zones (KEK) that balance 6.5% economic growth with environmental preservation. However, challenges such as fossil fuel dependency and cross-sectoral coordination require evidence-based recommendations in the form of green sukuk incentives, multi-stakeholder collaboration, and technological innovation to achieve net-zero emissions faster than the 2060 target.